EDITORIAL - Vongurai, Rawin (Scholar: Human Sciences, 2025)
The Scholar: Human Sciences, a journal encompassing the fields of humanities and social sciences, has earned acclaim in the Thailand Citation Index (TCI) as a prominent publication since 2015. It currently holds the esteemed TCI: TIER1 classification. We take great pride in presenting the latest issue, which features a collection of manuscripts that have undergone rigorous evaluation. Each submission has been meticulously reviewed through a blinded review process by three specialized reviewers from different institutions, both internal and external to the authors. This peer-reviewed accreditation ensures the scholarly quality and integrity of the published articles. This issue covers thirty-one articles. The first article titled “Assessing the Key Drivers of Sophomores’ Satisfaction and Learning Outcome in Shandong, China” explored the factors impacting student satisfaction and learning outcome, specifically among sophomore students at public colleges in Shandong, China, during the COVID-19 outbreak. The second article titled “Determinants of Teachers’ Job Performance: A Case of Zhanjiang University of Science and Technology, China” examined how eight independent variables (organizational commitment, innovative work behavior, big five personality traits, job satisfaction) impact the dependent variable (job performance). The third article titled “Implementing Intervention Design Program to Assess Teachers’ Job Satisfaction in Vocational and Technical College in Anhui, China” explored the factors influencing teachers’ job satisfaction at the Anhui Institute of Vocational Technology. The fourth article titled “A Study on The Main Influencing Factors of Turnover Intention of College Teachers in Zhanjiang City, China” examined the influencing factors of teacher turnover rate in Zhanjiang universities, China. The fifth articled titled “Determinants of Entrepreneurship Education Intention of Vocational College Students in Hunan, China” examined the determinants of the intention of vocational college students from a public college in Hunan, China, regarding entrepreneurship education. The sixth article titled “Influential Factors Affecting the Attitudes and Purchase Intentions of Post-90s Customers Towards Electric Vehicles in Nanning, China” explored the causal relationships among perceived usefulness, perceived ease of use, compatibility, personal innovation, environmental awareness, environmental attitude, and behavioral attitude. The seventh article titled “Exploring Interactive Pedagogy to Enhance Students’ Engagement in ECE in Southwest China” examined the significance between learner-content interaction, learner-instructor interaction, learner-learner interaction and students’ emotional, behavioural, and cognitive engagement in the classroom. The eighth article titled “Determinants of Students’ Performance in Higher Vocational Colleges under the Vocational Skill Evaluation System in Hangzhou, China” explored the relationship between student experience, academic culture, employability, compatibility with online mode, innovation, new opportunities, knowledge management process, and performance. The ninth article titled “Factors Impacting Teacher’s Job Satisfaction in Private Higher Education Schools in Beijing, China” focused on the teachers of Beijing City University to enhance their job satisfaction through the development of a teacher professional community, professional collaboration, and distributed leadership. The tenth article titled “An Examination on Influencers of Student Satisfaction with the Use of E-Learning in Higher Education in Hangzhou, China” examined the relationship between course content quality confirmation, reliability, responsiveness, empathy, course content quality, confirmation, perceived ease of use, and satisfaction of online learning. The eleventh article titled “The Driving Factors of Online Learning Satisfaction and Online Continuous Learning Intention Among Sophomores in Chengdu, China” studied the factors influencing satisfaction with online learning and the continuous learning intention among sophomore university students in Chengdu. The twelfth article titled “An Investigation on Influential Factors on Students’ Perceived Employability in Higher Education, Guangzhou, China” aimed to explore the impacting factors of the perceived employability of graduates from a vocational college in Guangzhou, China. The thirteenth article titled “Poetry In Motion -A Journey of Science, Technology, And Society (STS) Students to Creative Expression in Western Visayas, Philippine” aimed to determine the relationship between poems and songs in teaching some topics in Science, Technology, and Society (STS) in one of the state universities and colleges (SUCs) in Western Visayas, Philippines. The fourteenth article titled “Influential Factors on the Utilization of E-Learning Systems among Second-Year Arts Major Students in Higher Vocational Colleges in Henan, China” explored the factors impacting the use behavior of e-learning systems among second year of art majors in higher vocational colleges in Henan, China. The fifteenth article titled “Exploring Perceived Learning Impact of Students in School of Art Design and Animation Towards Massive Open Online Courses at a University in Sichuan, China” investigated factors influencing students’ perceived learning impact of massive open online courses at Sichuan university of media and communication, China. The sixteenth article titled “Leadership Behaviors Influencing Faculty Job Satisfaction at Private Universities in Zhanjiang: An Analysis of Strategic Interventions” investigated the impact of leadership behaviors on faculty job satisfaction in private universities in Zhanjiang, China. The seventeenth article titled “Improving Students’ Entrepreneurial Intention: A Case of Guangdong Ocean University China” aimed to explore the factors that influence entrepreneurial intention based on the current situation of Guangdong Ocean University to cultivate and improve students’ entrepreneurial intentions. The eighteenth article titled “The Aspects of Postgraduate Students’ Satisfaction and Intention to Use Online Higher Education from Public Universities in Guangdong, China” aimed to investigate the students’ satisfaction and willingness to attend online higher education at three universities in Guangdong Province. The nineteenth article titled “Driving Factors of Teachers’ Job Satisfaction in Private University in Zhanjiang University of Science and Technology, China” aimed to develop strategic plans from the perspectives of talent management, employee engagement, ongoing project participation, self-awareness, relationship transparency, internalized ethics, and balanced handling to enhance teacher job satisfaction. The twentieth article titled “Pupils’ Bullying at School Is Not Related to Child-Parent Relationship: Empirical Evidence from the Philippines” investigated the extent of bullying among sixth grade pupils at a public school in Negros Oriental, Philippines, and analyze whether or not bullying at school among pupils is related to child-parent relationship. The twenty-first article titled “Factors Impacting Teachers’ Job Burnout in a Private University in Zhanjiang, China” aimed to explore the impact of factors such as teachers’ background, social support, social-emotional ability, teacher-student relationships, emotional exhaustion, depersonalization, and reduced personal accomplishment on teacher burnout at a private university in Zhanjiang, China. The twenty-second article titled “Exploring College Students’ Satisfaction in Cloud-Based Electronic Learning in Chengdu, China” aimed to explore the factors impacting college students’ perceived usefulness, cognitive absorption, and satisfaction in cloud-based electronic learning in Chengdu, China. The twenty-third article titled “Key Factors Influencing Male Undergraduate Students’ Behavioral Intentions Towards Mobile Library Platforms in Chengdu, China” aimed to examine the primary factors that influence the behavioral intention of male undergraduate students toward mobile library platforms (m-library) in private universities in Chengdu, China. The twenty-fourth article titled “Predicting University Students’ Satisfaction and Continuance Intentions to Use AI-Powered Chatbots in Chengdu, China” aimed to investigate the determinants of university students’ satisfaction and continuance intentions toward AI-powered chatbots in Chengdu, China. The twenty-fifth article titled “Influential Factors Shaping the Behavioral Intention of Undergraduate Students towards Livestream Shopping in Chengdu, China” intended to investigate the factors influencing the choice of live shopping among students in Chengdu. The twenty-sixth article titled “The Examination on Students’ Parasocial Interaction and Brand Preference to Use Video Application in New Developing Area of Chengdu, China” provided valuable insights for content creators, video platform developers, and marketers seeking to effectively engage with and target this demographic in Chengdu, China. The twenty-seventh article titled “Influential Factors on English E-Learning Behavioral Intention and Usage Among Undergraduates at Chengdu University, Sichuan, China” investigated factors impacting the E-learning Behavioral Intention and Use behavior of undergraduates in non-English majors of Chengdu University who represent the undergraduates of Sichuan Province in China. The twenty-eighth article titled “Factors Influencing American Tourists’ Behavioral Intentions and Use Behavior of Tourism Apps” investigated the factors influencing American tourists’ behavioral intention and use behavior of tourism apps. The twenty-ninth article titled “Factors Impacting E-Commerce Platform’s Satisfaction and Repurchase Intention in Chengdu, China” investigated the primary determinants that significantly influence individuals’ satisfaction and intentions for repeat purchases in Chengdu, China. The thirtieth article titled “The Assessment on Factors Impacting Small & Micro Corporate Clients’ Behavioral Intention and Use Behavior of Accounting Information System in Dazhou, China” delved into the determinants of behavioral intention and use behavior of small & micro corporate clients towards accounting information systems among enterprises in Dazhou, China. The thirty-first article titled “Investigating the Impacts of Social Fitness Activities on Mental Health and Wellbeing of Undergraduate Students” examined the impact of social fitness activities on the mental health of undergraduate students.